Noise controlled semiconductor optical amplifiers - Lennox, Robert (Trinity College (Dublin, Ireland). School of Physics, 2012)
Semiconductor optical amplifiers (SOA) have been widely used in communications systems for decades, in a multitude of capacities. In their simplest form SOAs offer cost effective linear amplification at a variety of wavelengths, simultaneously covering a large gain bandwidth, with the added benefit of practical photonic integration. They are electrically pumped and have good thermal stability, all packaged within a very small volume. In addition to this, SOAs can be operated as non-linear entities under saturation, with the capability to perform alloptical functional duties over a range of configurations and data rates far beyond the realm of commercial high-speed electronics currently used for signal processing. These latter attributes are becoming ever more important as our appetite for digital information drives bandwidth consumption to greater heights.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin.